Mahmud Esad Seydişehri’nin fıkıh düşüncesi - Altıntaş, Emre (My University, 2010)
Seydişehrî, Fıkıh, İctihad ÖZET MAHMUD ESAD SEYDİŞEHRÎ’NİN FIKIH DÜŞÜNCESİ Mahmud Esad Seydişehrî, Osmanlı Devleti’nin son yarım asrında yaşamış önemli bir kişidir. Hukuk-ı Aile Kararnamesi’ni hazırlayan komisyona başkanlık etmiştir. İslam tarihi, hadis, dinler tarihi, fıkıhla ilgili çok sayıda kitap yazmıştır. Islah, tecdid, banka, sigorta, ictihad kapısı gibi on dokuzuncu yüzyılın önemli tartışma konularında fikirlerini ortaya koymuştur. Fıkıh düşüncesi eklektik bir yapıya sahiptir. Seydisehrî, Fiqh, Ijtihad

THE FIQH THOUGHT OF MAHMUD ESAD SEYDİSEHRÎ Mahmud Esad Seydisehrî, is an important man who lived in the Ottoman Empire’s last half century. He presided to the comission which preapered the decree of family law. He wrote a lot of books about history of Islam, hadith, history of religious, fiqh. He put forwarded his opinions about nineeth century’s important debate issues like ıslah, tejdid, bank, insurance, door of ijtihad. His fiqh thouhgt has an eclectic structure.
Keywords: Fıkıh; İslam